Effects of optimism on defensive pessimists. - Lin, Minghan. (2009)
This research explored the existence of optimism’s detrimental effects on individuals who consistently adopt a defensive pessimistic approach in an achievement-related setting. Data was collected from 60 undergraduates using established self-report measures of resilience, defensive pessimism, optimism, and anxiety. Statistical analysis of the participant scores provided evidence that the use of defensive pessimism is neither superior, nor inferior to the use of strategic optimism where achievement is concerned. A significant positive relationship was found between anxiety and defensive pessimism, indicating that anxiety plays a fundamental role in the defensive pessimism strategy. Results also suggest that optimism interferes with defensive pessimism, which reduces the overall effectiveness of the defensive pessimism strategy in coping with achievement-related situations.